2023
DOI: 10.3389/fenvs.2023.1119605
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation–soil dynamics in an alpine desert ecosystem of the Qinghai Lake watershed, northeastern Qinghai–Tibet Plateau

Abstract: Different types of dunes cause habitat differences, which can affect vegetation growth. In turn, water utilized by vegetation leads to the differential distribution of soil moisture in different dunes. However, vegetation–soil dynamics in the alpine desert of the Qinghai–Tibet Plateau remain poorly understood. We chose the largest section of desert along the eastern shore of Qinghai Lake as a study area to test the hypotheses that plant community characteristics and soil physicochemical properties show differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…The difference in temperature between the soil shallow layer and the frozen layer would result in a vertical transportation in soil water [ 68 ]. Previous study also suggested that there is an obvious vertical differentiation pattern in soil water on the QTP [ 69 ]. But soil water dynamic is simplified in the BBGC, as only one soil layer is defined.…”
Section: Discussionmentioning
confidence: 92%
“…The difference in temperature between the soil shallow layer and the frozen layer would result in a vertical transportation in soil water [ 68 ]. Previous study also suggested that there is an obvious vertical differentiation pattern in soil water on the QTP [ 69 ]. But soil water dynamic is simplified in the BBGC, as only one soil layer is defined.…”
Section: Discussionmentioning
confidence: 92%